Investigation of the aerodynamic parameters simulation method of a guided rocket. (June 2018) - Chen, Yong-Chao; Gao, Xin-Bao; Gao, Min
Orthogonal design method is adopted to investigate the aerodynamic parameters simulation method of a canard guided rocket, in order to obtain one simulation method which can calculate the aerodynamic parameters quickly, reliably, and accurately. The turbulence model, mesh size, y + value and flow field size, which are regarded as the main factors in computational fluid dynamics (CFD) simulation, are divided into three levels for comparative analysis. Nine simulation combination schemes, which are representative and comprehensive, are singled out based on orthogonal table. The axial force coefficient and normal force coefficient in subsonic, transonic, and supersonic conditions are respectively calculated with these nine simulation combination schemes. The best simulation combination schemes in subsonic, transonic, and supersonic conditions are respectively picked out by intuitive analysis and synthesis balance analysis. The aerodynamic parameters in different velocities and attack angles, which were obtained by corresponding best simulation combination schemes, prove that the best simulation combination schemes are accurate. The results provide basis for the aerodynamic characteristic study of the canard guided rocket, and this research method can be used for the investigation on aerodynamic parameters simulation method of projectiles with different configurations.